Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1017/s1463423613000492
|View full text |Cite
|
Sign up to set email alerts
|

‘Chaplains for well-being’ in primary care: analysis of the results of a retrospective study

Abstract: a substantial improvement in WEMWBS scores (mean=9 points, BCa 95% CI [7.23, 10.79], P=0.001) post-intervention. The improvement in scores was highest for those with initially lower levels of well-being. There is therefore evidence that chaplaincy interventions correlate with an improvement of holistic well-being as measured by a WEMWBS score. A prospective study on a larger scale would provide more detailed information on the interaction of possible variables. Further study is also required to evaluate the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
(40 reference statements)
5
27
1
Order By: Relevance
“…In the first phase of the study represented here, a quantitative retrospective analysis of patient data found evidence for a significant improvement in patient well-being scores (Kevern & Hill, 2014). However, the mechanisms or sources of this improvement were not immediately explicit, indicating the need to interview patients who had accessed the service.…”
Section: Chaplaincy In the Uk Contextmentioning
confidence: 90%
“…In the first phase of the study represented here, a quantitative retrospective analysis of patient data found evidence for a significant improvement in patient well-being scores (Kevern & Hill, 2014). However, the mechanisms or sources of this improvement were not immediately explicit, indicating the need to interview patients who had accessed the service.…”
Section: Chaplaincy In the Uk Contextmentioning
confidence: 90%
“…People who saw the chaplain more than four times scored higher still. Again, these findings are difficult to explain, especially since the only comparable data showed no relationship between wellbeing scores and number of visits (Kevern and Hill 2015). As above, these apparent trends will be examined in further detail using a pre-post method.…”
Section: Discussionmentioning
confidence: 93%
“…Flannelly et al (2012) used 'big data' to show that there were lower death rates in hospitals that employed chaplains than in those that did not. Kevern and Hill (2015) used survey methods to show that chaplains improved the wellbeing of people in primary care. In a retrospective review, Macdonald (2017) found primary care chaplains to be as effective as antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps for this reason, the idea and practice of spiritual care has gained only uneven acceptance. It is well established in Palliative Care (which has religious roots) (Department of Health 2010) but has less purchase in Primary and Acute Care (Cockell & McSherry, 2012;Mowat et al, 2012;Kevern & Hill, 2015). There is also a significant dissonance between the official position of healthcare providers and professional bodies, which remain broadly favourable to the idea of spiritual care, and its teaching and delivery (Balboni et al, 2014;Rushton, 2014;Lewinson et al, 2015;McSherry & Ross, 2015;Nascimento et al, 2016).…”
Section: Introductionmentioning
confidence: 99%